Effect of comorbidities and polypharmacy on fall risk among older adults - Mahmoud, Hend F; Elmedany, Hebatullah EMZ (International Journal of Human and Health Sciences (IJHHS), 2022)
Introduction: Fall is considered by far one of the leading causes of morbidity and mortality in the elderly population. Fall is almost always multifactorial. This study looks into the relation between different comorbidities, polypharmacy and falls. Methods: A descriptive and prospective study, the study population comprised 150 elderly patients aged > 60 years old, males and females, patients with previous history of falls are excluded. Comorbidity burden, polypharmacy and risk of falls were assessed. Results and Discussion: There was a significant positive correlation between Number of comorbidities, medications and risk of falls and there was a significant association between high risk of falls and presence of DM, PVD, OLD CVA and UI. Also, there was a significant positive correlation between age and risk of falls. Conclusion: Multiple comorbidities, polypharmacy and increasing age increase risk of falls. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 75-79